Coats Plus syndrome: a diagnostic and therapeutic challenge in pediatric gastrointestinal hemorrhage - Hoşnut, Ferda Özbay; Şahin, Gülseren; Akçaboy, Meltem (The Turkish Journal of Pediatrics, 2022)
Background. Cerebroretinal microangiopathy with calcifications and cysts formerly known as Coats plus syndrome is a rare multisystemic autosomal recessive disease that affects the eyes, brain, bone, and gastrointestinal system. Intestinal telangiectasia are components of vascular malformations characterized by gastrointestinal system bleedings. Recurrent gastrointestinal system bleedings have been reported as being due to hepatic failure or vascular malformations of the gastrointestinal system tract. Case. Here we report a patient who presented with recurrent gastrointestinal system bleeding episodes, bilateral exudative retinopathy, intracranial calcification and was diagnosed with Coats plus syndrome. Recurrent gastrointestinal system bleeding was controlled by monthly octreotide treatment. Conclusions. Coats plus syndrome presenting with vascular malformations should always be kept in mind in a patient with recurrent gastrointestinal bleeding and accompanying systemic physical findings. Octreotide treatment is an important option for patients with life threatening gastrointestinal system bleeding. Long term use of octreotide treatment can be used successfully in selected pediatric cases.